Peran Bank Jatim Syariah Dalam Meningkatkan Profitabilitas - Agus Wahyu Irawan; Imam Wahyudhi (Universitas Islam Darul 'ulum Lamongan, 2023)
This research has a problem about the role of Islamic Jatim banks in increasing profitability. The research method used by researchers is a qualitative descriptive research method. The results that the researchers obtained were increasing financing (expansion of financing). By increasing financing to the public, the profits obtained by the bank will increase. Reducing operational costs. Reducing NPL (non-performing/uncollectible financing). effort. Bank Jatim Syariah is no exception, which is engaged in raising funds (funding) and channeling funds (landing) with a sharia pattern. Barriers in its implementation is bad credit. It is difficult to understand the character of customers in their technical philosophy, rejecting risky customers with all considerations is better than accepting them.